2021
DOI: 10.1080/1062936x.2021.1960601
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling on SARS-CoV-2 papain-like protease: an integrated study with homology modelling, molecular docking, and molecular dynamics simulations

Abstract: Table S1. Databases and software used and their detailed information. Database Name Version Website links References NCBI database Update 2021 https://www.ncbi.nlm.nih.gov/ [1] BLAST database

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…From our docking simulation, we suggested that three ligands, i.e., diposphoryl lipid A, FC-core lipid A, and Kdo2 lipid A, can be activators of the factor C protein by binding to the region of the receptor to form a ligandreceptor complex. Therefore, three structures (complexes 2, 3, and 4) were selected for further analysis [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our docking simulation, we suggested that three ligands, i.e., diposphoryl lipid A, FC-core lipid A, and Kdo2 lipid A, can be activators of the factor C protein by binding to the region of the receptor to form a ligandreceptor complex. Therefore, three structures (complexes 2, 3, and 4) were selected for further analysis [45].…”
Section: Discussionmentioning
confidence: 99%
“…From this figure, all complexes involved fluctuations during the simulation. The fluctuation along simulation can be influenced by atomics interactions in the system via electrostatic interaction and hydrogen and hydrophobic interactions which involve structural rearrangement at the protein and ligand molecule interface [22,45]. Moreover, the factor C protein has a large structure (1019 amino acids) with several domains placing different regions which make the protein structure tend to fluctuate along the MD simulation.…”
Section: Discussionmentioning
confidence: 99%
“… 25 The docking parameters were computed according to similar protocols to our previous works. 26 - 28…”
Section: Methodsmentioning
confidence: 99%
“…In performing molecular docking, a grid box parameter is required to decide the positional and rotational of the ligand into the moiety of the receptor (Arwansyah et al 2021a). The grid box was constructed using 24 × 24 26 points and a grid spacing of 1.00 Å.…”
Section: Molecular Dockingmentioning
confidence: 99%